The balance of elements in the system “Luvic Chernozems – agricultural plants” on the Plavsk upland (Tula region of Russia) - O. V. Shopina (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
To assess the transfer of macro (K, P, S, Mg, Ca, as well as Si, Na, Fe, Al, Mn and Ti) and microelements (Zn, Ba, Cu, Sr, Mo, as well as As, Zr, Pb, Co, Ni, V and Cr) from Luvic Chernozems (Aric, Loamic, Pachic) into agricultural plants, we studied the inventories of chemical elements in three agrocenoses (wheat, soybean, Galega orientalis Lam. and Bromopsis inermis Leyss grass mixtures) from the Plavsk upland (Tula Region). This territory is subjected to intensive industrial and agricultural impacts: it is 40 km away from the town of Shchekino with a nitrogen fertilizer plant and a thermal power plant, 60 km away from Tula with large metallurgical enterprises, 70 km away from the town of Novomoskovsk with several chemical enterprises and state district power plant. In soils, the total content of elements was determined by the X-ray fluorescence spectrometry. The elemental composition of plants after autoclave decomposition with a mixture of concentrated nitric acid and hydrogen peroxide and the content of the bioavailable fraction (extracted by an ammonium acetate buffer with pH 4.8) of elements in soil were estimated by the atomic emission spectrometry with inductively coupled plasma. In topsoil (a 10-cm layer), maximal inventories are typical for total Si (40 ± 4 kg/m2), Al (7.0 ± 0.8 kg/m2) and Fe (3.4 ± 0.3 kg/m2) and for bioavailable Ca (570 ± 48 g/m2), Mg (43 ± 4 g/m2), K (22 ± 6 g/m2). In plants, the main inventories (g/m2) of K, P, S, Mg, Si, Mn, Zn, Ba, Cu, Mo occur in the above ground phytomass. The most effectively plants assimilate bioavailable fractions of K, P, Ti, Mo, As, Zr, V. Based on the resource method for soil quality assessment, the studied Chernozems are characterized by a low level of Ni contamination, a moderate supply of bioavailable K with a lack of bioavailable P.